HPV, protein p16 and squamous cell carcinoma of the oral cavity - Blahák, Jiří; Zelinka, Jiří; Gumulec, Jaromír; Macháček, Ctirad; Daněk, Zdeněk; Bulik, Oliver (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
BACKGROUND: Squamous cell carcinoma of the oral cavity is generally caused by the long-term impact of known risk factors, e.g. tobacco and alcohol, along with chronic traumatisation. A number of studies now implicate HPV infection in head and neck tumour carcinogenesis but the exact role of HPV infection in the oral cavity remains unclear. METHODS: In this study, we evaluated 78 patients with oral squamous cell carcinoma (OSCC) for the expression of protein p16 in the context of HPV positivity and its influence on the overall survival rate, disease location, staging and grading. RESULTS: Regarding the tumour location, no significant difference was found between HPV-positive and HPV-negative patients, nor between p16-positive and p16-negative patients. There was also no trend in terms of HPV status and stage, and differentiation of carcinoma. There was no effect on HPV-positive patients relative to the time to progression (P=0.84) and overall survival rate (P=0.78). P16 positivity was not found to have an effect on the overall survival rate of patients (P=0.41) and there was no correlation between p16 positivity relative to the time to progression (P=0.66). CONCLUSIONS: In summary, the data suggest that there is no effect of HPV status on the prognosis of OSCC patients compared to other HNSCC locations.
Keywords: nádory úst; Aged; Mouth Neoplasms; lidé středního věku; senioři; prognóza; infekce papilomavirem; Survival Rate; lidé; Papillomavirus Infections; Middle Aged; Prognosis; Female; Male; ženské pohlaví; Humans; Cyclin-Dependent Kinase Inhibitor p16; mužské pohlaví; inhibitor p16 cyklin-dependentní kinasy; míra přežití; spinocelulární karcinom; Carcinoma, Squamous Cell